SCREENING OF DIFFERENT TOMATO GENOTYPES/VARIETIES AGAINSTTOMATO EARLY BLIGHT CAUSED BY ALTERNARIA ALTERNATA (Journal of Plant Disease Sciences, 2025)
Tomato (Lycopersicon esculentum Mill.) is one of the most remunerative and widely grown vegetables in the world.  This crop is affected by major fungal pathogens (viz., early blight, late blight, wilt, collar rot, damping off and powdery mildew), among them early blight (Alternaria alternata) is considered as most important one. A field screening was conducted to evaluate fifteen tomato genotypes for their reaction to Early blight. The results revealed that four genotypes, namely JTL-23-07, JTR-23-12, JTL-23-10 and JTL-23-03, exhibited a moderately resistant (MR) reaction. Seven genotypes (JTL-23-02, JTL-23-13, JTL-23-11, JTL-23-09, JTL-23-06, JTL-23-04 and JTL-23-08) were moderately susceptible (MS), while four genotypes (JTL-23-01, JTL-23-14, JTL-23-05 and GT-6) were classified as susceptible (S). Among the tested materials, the moderately resistant genotypes can serve as potential sources for resistance and may be effectively utilized in future breeding programs to develop cultivars resistant to Early blight in tomato.
Keywords: Alternaria alternata, Early blight, Genotype, Tomato